Interdisciplinary research on periodontitis and depression: a bibliometric analysis of research trends, hotspots and future directions - Tang, Qian; Xu, Weiye; Zhang, Fushen; Yuan, Guangyi; Zhou, Dian (Frontiers in Oral Health, 2025)
BackgroundPeriodontitis, a chronic inflammatory disease affecting nearly 50% of the global population, has been increasingly linked to depression, a prevalent psychiatric disorder.MethodsThis study conducted a comprehensive bibliometric analysis to explore the association between periodontitis and depression, from 2000 to 2024 via the Web of Science Core Collection (WoSCC) database. Bibliometric parameters were extracted and bibliometric analysis was conducted via VOSviewer, and CiteSpace software.ResultsA total of 205 publications, comprising 173 original articles and 32 reviews, were analyzed via VOSviewer and CiteSpace, with a focus on countries, institutions, authors, journals, keywords, and citations. The results revealed a significant increase in publications, with notable contributions from China, the USA, and Brazil, accounting for 43.9% of all studies. The collaborative networks highlight the growing interdisciplinary nature of this field. “Depression” (n = 71), “disease” (n = 66), “association” (n = 50), “oral health” (n = 47) and “stress” (n = 37) were the most frequent keywords, reflecting current research hotspots. Through the time map analysis of keyword clustering, we found that the research hotspots gradually changed from “risk factors”, “chronic periodontitis” and “psychosocial factors” to “inflammation”, “Alzheimer's disease” and “smoking” and other keywords. Keyword analyses identify emerging research hotspots, including the interplay of stress, anxiety, and inflammation.ConclusionThe number of related studies on periodontitis and depression continues to increase. The analysis of countries, authors and keywords reveals development trends, collaboration opportunities, and priority themes such as psychosocial factors and systemic inflammation. These findings provide a theoretical foundation for future research on periodontitis and depression.